Safety, Efficacy, and Cost Savings of Single Parathyroid Hormone Measurement for Risk Stratification after Total Thyroidectomy. Issue 8 (August 2013) - McCullough, Meghan; Weber, Collin; Leong, Chris; Sharma, Jyotirmay
The management of hypocalcemia (HC) after total thyroidectomy (TTx) is a challenge as TTx is transitioned into a same-day surgery. Measurement of parathyroid hormone (PTH) level after TTx may allow for prediction of postoperative HC and lead to shorter hospital stays. A prospective database was queried between January 2010 and June 2012 with 95 patients who had undergone TTx identified. Patient demographics; preoperative diagnosis; laboratory values and cost; complications; intravenous calcium supplementation; and length of stay (LOS) were analyzed. A PTH-based algorithm was retrospectively applied and theoretical cost savings were analyzed in terms of laboratory cost, LOS, and total cost. Ninety-five patients underwent TTx: 37 patients (38.9%) had cancer, whereas 27 (28.4%) had Graves' disease and the remaining 31 (32.6%) had a benign multinodular goiter. Postoperative PTH was recorded in 72 patients (74.4%); 46 (63.8%) had PTH greater than 10 pg/mL and 26 (36.9%) had PTH less than 10 pg/mL. Transient HC occurred in 10 patients (38.4%) with PTH less than 10 pg/mL (relative risk, 17.69; P = 0.0001). Patients with PTH less than 10 pg/mL incurred a 14.9 per cent higher hospital cost compared with those with PTH greater than 10 pg/mL. With retrospective implementation of the algorithm, there is a potential 46.4 per cent cost savings for the PTH less than 10 pg/mL group, 67.3 per cent savings for the PTH greater than 10 pg/mL group, and 46.7 per cent savings when taken altogether. Algorithmic risk stratification based on postoperative PTH less than 10 pg/mL serves as both a sensitive (100%) and specific (76.7%) predictor of postoperative HC. Such risk stratification may allow for same-day discharge in a number of patients, and even in patients requiring an overnight stay, result in cost savings as a result of a reduction in laboratory expenditures.